Tracheal nodularity and paratracheal soft tissue nodule: post-radioactive iodine treatment changes with peculiar visual and pathologic findings in a case of metastatic follicular variant papillary thyroid carcinoma: a case report - Benjamin L. Sievers; Wangpan Shi; Jingjing Hu; Russell Miller; Niral M. Patel; Keriann Van Nostrand; George Z. Cheng; Charles H. Choe; Jorge Alberto Muñoz Pineda (Journal of Medical Case Reports)
Abstract Background Follicular variant papillary thyroid carcinoma is a distinct subtype of papillary thyroid carcinoma that can occasionally present with aggressive features, including distant metastases and extrathyroidal extension. While radioactive iodine ablation is a well-established treatment for residual disease, its post-treatment effects on tracheal and paratracheal structures remain poorly characterized. Case presentation A 22-year-old male individual of Taiwanese descent presented with an enlarged neck mass and was diagnosed with follicular variant papillary thyroid carcinoma. He underwent thyroidectomy, modified radical neck dissection, and postoperative radioactive iodine-131 ablation (100 mCi). A total of 1 year later, a chest computed tomography revealed a paratracheal soft tissue nodule and tracheal nodularity. Bronchoscopy with endobronchial ultrasound-guided sampling identified multiple 2–3 mm submucosal tracheal nodules containing white exudate. Cytopathologic analysis of both the paratracheal soft tissue nodule and the tracheal wall nodules revealed mucinous material without evidence of malignancy or inflammation. Microbiologic studies were negative for infection. Conclusion These atypical bronchoscopic and pathologic findings likely represent post-radioactive iodine treatment changes. The patient remained without evidence of disease for 22 months, ongoing on thyroid suppression levels of thyroxine hormone replacement. The case represents successful radioactive iodine treatment of papillary thyroid carcinoma residual disease after surgical resection, with the first described pathologic findings to correlate with these post-treatment changes.